Análise comprativa do desempenho de índices de seca aplicados à região do Alto Jaguaribe - Ceará - Ferreira, Luciana Kamila Rodrigues (2016)
Drought is a natural phenomenon that can bring immeasurable consequences to activities human, mainly because it is a lasting phenomenon, without beginning and end certain. In this context, several scholars have been trying to get means for the determination and forecast drought, based on the measurement data, namely precipitation, humidity soil, air humidity, among others. In the context of Ceará, where drought is a phenomenon well this in view that this is a semi-arid region and have low rainfall and high evaporation rates, a sub-basin was chosen, the high Jaguaribe, to present many Concise data and representing the first sub-basin covered by the river Jaguaribe, which is a representative river to the state. A literature review was conducted for the choice of more applicable indices to climatic characteristics of the region, namely: Severity Index Herbst (HSI) and Dry Index Bhalme and Mooley (BMDI), applied to the entire historical series two rainfall stations distributed in the sub-basin. The results obtained were compared to their performance indices applied to a smaller series, to evaluate the feasibility of using these indexes in regions with poor data. The index that best set for two data sets was the HSI.